Fusarioid community diversity associated with conifer seedlings in forest nurseries across the contiguous USA - Dobbs, J. T.; Kim, M.-S.; Reynolds, G. J.; Wilhelmi, N.; Dumroese, R. K.; Klopfenstein, N. B.; Fraedrich, S. W.; Cram, M. M.; Bronson, J.; Stewart, J. E. (Frontiers in Plant Science, 2023)
Fusarioid fungi that cause damping-off and root diseases can result in significant losses to conifer crops produced in forest nurseries across the USA. These nurseries are vital to reforestation and forest restoration efforts. Understanding the diversity of Fusarioid fungi associated with damping-off and root diseases of conifer seedlings can provide an approach for targeted management techniques to limit seedling losses and pathogen spread to novel landscapes. This study identifies 26 Fusarium spp. (F. acuminatum, F. annulatum, F. avenaceum, F. brachygibbosum, F. clavus, F. commune, F. cugenangense, F. diversisporum, F. elaeagni, F. elaeidis, F. flocciferum, F. fredkrugeri, F. fujikuroi, F. grosmichelii, F. ipomoeae, F. lactis, F. languescens, F. luffae, F. odoratissimum, F. oxysporum, F. queenslandicum, F. redolens, F. torulosum, F. triseptatum, F. vanleeuwenii, & F. verticillioides), 15 potential species within Fusarium and Neocosmospora species complexes (two from F. fujikuroi species complex, nine from F. oxysporum species complex, three from F. tricinctum species complex, and one from Neocosmospora species complex), and four Neocosmospora spp. (N. falciforme, N. metavorans, N. pisi, & N. solani) and associated host information collected from conifer-producing nurseries across the contiguous USA. Phylogenetic analyses identified Fusarioid fungi haplotypes that were associated with 1) host specificity, 2) localization to geographic regions, or 3) generalists found on multiple hosts across diverse geographic regions. The haplotypes and novel species identified on conifer seedlings should be considered for further analysis to determine pathogen spread and assess management practices.